2017
DOI: 10.1093/ejcts/ezw400
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of occult pN2 disease following resection and mediastinal lymph node dissection in clinical stage I lung cancer patients

Abstract: Sixteen percent of pN2 patients had mediastinal lymph node metastasis beyond the lobe-specific lymphatic drainage. We recommend a complete lymphadenectomy be performed, even in clinical stage I NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 32 publications
4
64
0
2
Order By: Relevance
“…It has been widely recognized that adequate lymph node assessment plays a vital role in the accurate staging and prognostic evaluation of NSCLC patients, for which SLND has been universally recommended and accepted . However, because of an increase in the detection of early‐stage lung cancer, some scholars have advocated that this classic approach might not be necessary for all early‐stage lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely recognized that adequate lymph node assessment plays a vital role in the accurate staging and prognostic evaluation of NSCLC patients, for which SLND has been universally recommended and accepted . However, because of an increase in the detection of early‐stage lung cancer, some scholars have advocated that this classic approach might not be necessary for all early‐stage lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this subgroup, all metastatic lymph nodes were in so-called lobe-specific stations [3]. The median number of involved nodes was 2.…”
Section: Resultsmentioning
confidence: 83%
“…Occult N2 disease was detected in 9% of these patients (146/1,667), and risk factors for occult N2 disease were histology (adenocarcinoma) and vascular invasion. Skip metastases (defined as N2 lymph node involvement without N1 involvement) was observed in 34% of patients with pN2 disease (47/139), and 16% of patients with occult N2 disease had mediastinal lymph node metastases beyond the extent of L-SND (6 with RUL tumors and 2 with LUL tumors had metastasis to station 7; 6 with RLL tumors had metastasis to station 2R or 4R; and 8 with LLL tumors had metastasis to station 5 or 6); consequently, it was concluded that SND should be performed even in surgery for clinical stage I NSCLC (18). The rate of occult N2 was similar and the rate of skip metastasis was higher compared to previous reports (19).…”
Section: Editorialmentioning
confidence: 99%